EPR study of Mn-implanted single crystal plates of TiO2 rutile - Guler, S.; Rameev, B.; Khaibullin, R. I.; Lopatin, O. N.; Aktas, B. (Elsevier, 2010)
Single crystals of Mn-implanted TiO2 rutile have been investigated by electron paramagnetic resonance (EPR) technique at room temperature. We have observed an EPR signalon Mn4+ ions (S=3/2) in the manganese-implanted single crystal TiO2 plates. Besides, weaker EPR signals due to Fe3+(S=5/2, L=0) and Cr3+(S=3/2) ions have also been observed. Characteristic six-line splitting of the manganese EPR lines due to hyper-fine interaction with Mn-55 nuclei( spin I=5/2) has also been observed. Analysis of the EPR spectra shows that the manganese, iron and chromium ions substitute for Ti4+ ions in the TiO2 rutile host. Two structurally equivalent groups of the centers have been observed in the EPR spectra in correspondence with two octahedral positions of the Ti ions in the rutile structure. Spin Hamiltonian parameters for the crystal field of orthorhombic symmetry on the Mn4+, Fe3+ and Cr3+ centers have been obtained as result of computer modelling. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electron paramagnetic resonance; Titanium dioxide; Ion implantation; Diluted magnetic oxide; Spintronic